Knowledge, Attitude, Practise of Presbyopia Among Health Care Workers in Tertiary Health Care - Mattaparthi Gnaneswari; Syeda Sadiya Ikram; Sanjeev Kumar Puri (International Journal of Allied Medical Sciences and Clinical Research, 2022)
ABSTRACTAimTo determine the prevalence and to assess the level of knowledge, attitude, the practise of Presbyopia among health care workers in tertiary health care.Settings and Design:It was a hospital-based cross-sectional and questionnaire study conducted in the Outpatient Department Of Ophthalmology at Saveetha Medical College and Hospital from November 2021 to January 2022.Methods and Material:This study was done on 140 subjects in the age group between 40-60 years among health care workers, and it is approved by the Institutional Ethical Committee of Saveetha College of Allied Health Sciences.20 Structured pre and post-questionnaires were administered to all consenting health care workers and a video shown to determine the prevalence of Presbyopia and to assess the level of Knowledge, Attitude, the practice of Presbyopia. Visual acuity measured using Snellen's chart for distance and near. The eye with the better visual acuity was used for classifying the patients. Results: Based on our results we observe that the prevalence of Presbyopia was found to be 71% and based on assessment 77.1% of subjects heard about near vision loss in pre-assessment and 100% in post-assessment. About 89.2% of individuals thought the loss of vision was age-related in pre-assessment and 100% in post-assessment and 91.4% were aware that treatment of Presbyopia is glasses in pre-assessment and 100% in post-assessment. The major reason for not wearing spectacles was difficult to assess is about glasses 37.8%.Conclusion:High prevalence of Presbyopia was seen with the majority of them uncorrected due to lack of awareness 33.5%, difficult to assess37.8%, lack of felt needed28.5%, Therefore Awareness was created about Presbyopia among health care workers. Ensuring adequate treatment of Presbyopia among health care workers can impact positively the quality of life and productivity of health personnel.Keywords: Presbyopia, Visual Acuity, age-related, attitude.